Effect of lime application, harvest and drying on the sanitary quality of dry-season peanut - Rossetto, Claudia Antonia Vieira; Lima, Tatiana de Moraes; Viegas, Élson de Carvalho; Silva, Otniel Freitas; Bittencourt, Anna Maria (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effect of liming, harvest period and drying method on the sanitary quality of peanut (Arachis hypogaea L.) cv. Botutatu, cultivated in the field in the dry season. The experimental design was a split split plot replicated four times in completely randomized blocks. Lime levels (0.0 and 1.8 ton/ha) were applied in the plots, four different harvesting periods starting at 104 days after planting were assigned to the split plots and two conditions of drying (forced air oven at 30oC and ambient at 24oC and 60% of relative humidity) were attributed to the split split plots. Populations of soil fungus and fungus associated to the seeds and to the pods and aflatoxin production potential were evaluated at each harvest. There was no effect of liming on the Aspergillus spp. population in soil as well as on the pods and seeds. The delay at the time of harvest provides contamination increase of Aspergillus flavus in the pods and in G1 and G2 aflatoxin production; the drying conditions in ambient propitiate larger incidence for Rhizopus spp. in the pods and smaller incidence for Aspergillus flavus in the seeds.